Correlations redux. [article]. - Olkin, Ingram
Correlational analysis is a cornerstone method of statistical analysis, yet most presentations of correlational techniques deal primarily with tests of significance. The focus of this article is obtaining explicit expressions for confidence intervals for functions of simple, partial, and multiple correlations. Not only do these permit tests of hypotheses about differences but they also allow a clear statement about the degree to which correlations differ. Several important differences of correlations for which tests and confidence intervals are not widely known are included among the procedures discussed. Among these is the comparison of 2 multiple correlations based on independent samples. --(from the author).